Market efficiency and news dynamics: Evidence from international equity markets - Thomas C. Chiang (Economies, 2019)
This paper examines the efficient market hypothesis by applying monthly data for 15 international equity markets. With the exceptions of Canada and the U.S., the null for the absence of autocorrelations of stock returns is rejected for 13 out of 15 markets. The evidence also rejects the independence of market volatility correlations. The null for testing the absence of correlations between stock returns and lagged news measured by lagged economic policy uncertainty (EPU) is rejected for all markets under investigation. The evidence indicates that a change of lagged EPUs positively predicts conditional variance.
Keywords: 330; efficient market; economic policy uncertainty; random walk; news; Asian market; G7 market